Techno-economic evaluation of a combined bioprocess for fermentative hydrogen production from food waste. (February 2016) - Han, Wei; Fang, Jun; Liu, Zhixiang; Tang, Junhong
Highlights: The techno-economic evaluation of H2 production from food waste was performed. The H2 price and labor cost have the highest impact on the net present value. The unit production cost of hydrogen obtained from this study was US$1.02/m 3 . The plant would shutdown with food waste feed less than 0.3 ton/day. Abstract: In this study, the techno-economic evaluation of a combined bioprocess based on solid state fermentation for fermentative hydrogen production from food waste was carried out. The hydrogen production plant was assumed to be built in Hangzhou and designed for converting 3 ton food waste per day into hydrogen. The total capital cost (TCC) and the annual production cost (APC) were US$583092 and US$88298.1/year, respectively. The overall revenue after the tax was US$146473.6/year. The return on investment (ROI), payback period (PBP) and internal rate of return (IRR) of the plant were 26.75%, 5 years and 24.07%, respectively. The results exhibited that the combined bioprocess for hydrogen production from food waste was feasible. This is an important study for attracting investment and industrialization interest for hydrogen production from food waste in the industrial scale.